2016
DOI: 10.1007/s00270-016-1334-1
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDOPA PET/CT-Guided Radiofrequency Ablation of Liver Metastases from Neuroendocrine Tumours: Technical Note on a Preliminary Experience

Abstract: 18F-FDOPA PET/CT-guided RFA appears technically feasible, safe, and effective in patients with GEP-NETs and low-burden hepatic metastases. Further prospective studies are required to elucidate its precise role in tailored multimodality management of GEP-NET liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
(28 reference statements)
0
23
0
1
Order By: Relevance
“…TAE has most often been compared to TACE, but no statistically significant differences have been drawn[29,45]. The TACE-DEB outcomes seem promising but serious complications, such as bilomas and abscess formation, have been reported[66] and they led to the premature discontinuation of a phase-II trial as serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAE has most often been compared to TACE, but no statistically significant differences have been drawn[29,45]. The TACE-DEB outcomes seem promising but serious complications, such as bilomas and abscess formation, have been reported[66] and they led to the premature discontinuation of a phase-II trial as serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) and microwave ablation are the most favored techniques to address neuroendocrine liver metastases and 5-year OS rates of up to 53% have been reported[44]. Radiofrequency ablation and microwave ablation may be performed either percutaneously or laparoscopically as part of a multi-modality treatment (in association of surgery) or as alternative, for patients who are not eligible for major surgical procedure[45]. Ablative techniques are most effective in patients with a low tumor volume (lesions between 1 and 5 cm) and best indicated for a limited number of metastases (< 5-6 lesions)[8].…”
Section: Locoregional Treatmentsmentioning
confidence: 99%
“…Both studies and case reports have reported the successful use in patients with carcinoid syndrome of the control of the symptoms of the hormone-excess state by using: everolimus[•38]; PRRT[•56, 57, 66, 95, •96, •148]; liver-directed therapies including TACE/TAE[70, 72, •73, 77, 95, 98, 149]; radioembolization[70, 150, 151]; RFA[80, 81, 83, 95, 152]; by increasing the dosage of octreotide/Lanreotide in refractory cases[94, 97, 153–155]; use of cytoreductive surgery[23, 95, 156–160]; use of 131 I-MIBG[95, 105, 106, 108, 110, •161, 162164]; with the use of the tryptophan hydroxylase inhibitor, Telotristat[108, 113, 114, ••116, •117, 118, 119] and with pasireotide in octreotide resistant cases[•122]. …”
Section: Summary Of Recent Advances In Management Of Specific Hormmentioning
confidence: 99%
“…PET/CT imaging is generally indicated to guide in biopsies of bony or visceral lesions, as these lesions will have intense activity metabolically, which can be easily visualized on PET/CT, but poorly on other modalities like ultrasound, MRI, and CT. On the other hand, ultrasound, MRI, CT, and similar imaging modalities are usually used in the guidance of superficial or percutaneous biopsies. 2 PET/CT imaging modalities can also be used to guide biopsies of lesions that had been previously biopsied with other techniques (ultrasound or CT) and reached inconclusive results with high clinical suspicion. These lesions must, however, have high metabolic activity for this technique to work.…”
Section: Indications Of Pet/ct Guided Proce-duresmentioning
confidence: 99%
“…Therefore, allowing the opening of routes to directly performing procedures with PET/CT guidance. 2 This last technique is not as widely available as the previous ones, and it usually can only be done in specialized PET/CT interventional suites. 3 In this review, we will thoroughly discuss the indications, uses, and advantages of guiding biopsies with PET/CT techniques, with main focus on the field of oncology.…”
Section: Introductionmentioning
confidence: 99%